2002
DOI: 10.1095/biolreprod66.6.1853
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation and Function of the Fas/Fas Ligand System in Human Trophoblast Cells1

Abstract: Trophoblast rejection, which is characterized by increased apoptosis, is mediated by T helper (Th)-1, or proinflammatory, cytokines, whereas Th-2, or anti-inflammatory, cytokines confer immune protection and facilitate implantation. We investigated the role of both types of cytokines on the expression and function of the Fas/Fas ligand (FasL) apoptotic pathway in trophoblast cells. First-trimester human trophoblast primary-culture cells as well as A3 and HTR/8 trophoblast cell lines were treated with proinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
105
3
12

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 63 publications
6
105
3
12
Order By: Relevance
“…Indeed, increased concentrations of pro-inflammatory cytokines, such as TNF-a and interleukin (IL)-1 receptor antagonist, have been reported in pre-eclampsia [62][63][64] . Some of these cytokines have been shown to activate apoptotic genes, such as the Fas/FasL system 65,66 and Bcl-2 26 in trophoblast, leading to aberrant placental invasion, function and rejection. In a recent study, we demonstrated that antiinflammatory cytokines (IL-10 and IL-6) increased the resistance of trophoblast cells to Fas-mediated apoptosis, either by inhibiting Fas expression or by inducing Flice Like Inhibitory Protein (Flip) activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, increased concentrations of pro-inflammatory cytokines, such as TNF-a and interleukin (IL)-1 receptor antagonist, have been reported in pre-eclampsia [62][63][64] . Some of these cytokines have been shown to activate apoptotic genes, such as the Fas/FasL system 65,66 and Bcl-2 26 in trophoblast, leading to aberrant placental invasion, function and rejection. In a recent study, we demonstrated that antiinflammatory cytokines (IL-10 and IL-6) increased the resistance of trophoblast cells to Fas-mediated apoptosis, either by inhibiting Fas expression or by inducing Flice Like Inhibitory Protein (Flip) activation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we demonstrated that antiinflammatory cytokines (IL-10 and IL-6) increased the resistance of trophoblast cells to Fas-mediated apoptosis, either by inhibiting Fas expression or by inducing Flice Like Inhibitory Protein (Flip) activation. On the other hand, pro-inflammatory cytokines (TNF-a and interferon-g) increase trophoblast sensitivity to Fasmediated apoptosis 65 . In this study, we found that serum from pre-eclamptic patients rendered the trophoblast more sensitive to Fas-mediated apoptosis, suggesting that this biological effect may be mediated by pro-inflammatory cytokines which have been reported to be increased in the plasma/serum of women with pre-eclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…First Trimester Primary Trophoblast Cell Isolation and Culture-Primary trophoblast cells were isolated from first trimester placentas as previously described (2,3). Isolated first trimester trophoblast cells were cultured at 37°C/5% CO 2 in Dulbecco's modified Eagle's medium supplemented with 10% human serum (Gemini Bio-Products, Woodland, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The Fas/Fas ligand system represents one of the most common and well characterized TNF death receptor apoptotic pathways. Despite expressing both Fas and Fas ligand, trophoblast cells isolated from first trimester placentas are resistant to Fas-mediated apoptosis under normal conditions (1)(2)(3). However, in contrast to Fas ligand-induced apoptosis, first trimester trophoblast cells have been shown to be sensitive to TNF-␣-mediated apoptosis (1,2,4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation